2001
DOI: 10.1016/s0736-0266(00)00067-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of changes in mRNA levels of myoblast‐ and fibroblast‐derived gene products in healing skeletal muscle using quantitative reverse transcription‐polymerase chain reaction

Abstract: Changes in expression of type I l l al-collagen and myosin I1 heavy chains were characterized in rabbit skeletal muscle following single stretch injury using quantitative reverse transcription-polymerase chain reaction. Collagen 111 expression was highly elevated in the injured leg compared with the control limb both at the myotendinous junction and in the distal muscle belly. While upregulation of collagen I11 expression at the myotendinous junction was maximal on day 1. collagen 111 expression in the distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 15 publications
2
35
0
4
Order By: Relevance
“…Other growth factors and/or cytokines with higher molecular weights than VEGF may also become concentrated in the capsules. Reports that direct cell-cell interaction between fibroblasts induces expression of VEGF [24,25] also support the present results. However, encapsulated Sk-EECs showed copacetic proliferation and differentiation, thus further indicating that nutritional and other factors in the culture medium continuously affected Sk-EEC growth in the capsule, which suggests that low-weight molecules can pass through the HA-collagen capsule with relative ease, while larger molecules and/or vigorously expressed molecules accumulated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other growth factors and/or cytokines with higher molecular weights than VEGF may also become concentrated in the capsules. Reports that direct cell-cell interaction between fibroblasts induces expression of VEGF [24,25] also support the present results. However, encapsulated Sk-EECs showed copacetic proliferation and differentiation, thus further indicating that nutritional and other factors in the culture medium continuously affected Sk-EEC growth in the capsule, which suggests that low-weight molecules can pass through the HA-collagen capsule with relative ease, while larger molecules and/or vigorously expressed molecules accumulated.…”
Section: Discussionsupporting
confidence: 91%
“…The present Sk-EECs were isolated by the same methods as for Sk-34 cells [12][13][14][16][17][18], and they were not sorted (total cell fraction); thus, they included Sk-34 and other stem cells [13,14,16,17]. Skeletal muscle also includes fibroblasts in their connective networks [24,25], which may have contaminated the Sk-EECs and contributed to bFGF expression. For these reasons, concentrated VEGF and bFGF probably induced serial alignment of skeletal muscle derived myo-endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that scar tissue formation, along with weakness or atrophy of the previously injured muscle may be contributing factors to re-injury [8]. Indeed, prior animal models of injury have shown that muscle tissue may not be able to fully regenerate to pre-injury state, with connective scar tissue persisting at the site of injury indefinitely [18, 19]. Given that most hamstring strain injuries occur along the proximal musculotendon junction [20], where the muscle fibrils intersect with the tendon [17] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors and cytokines are potent mitogenic activators for very many cells, including MPC cells during the regeneration of injured muscle cells (24) . Therefore, these are promising therapeutic options for assisting in recovering the skeletal musculature.…”
Section: Muscle Injury -Physiopathology Diagnosis Treatment and CLImentioning
confidence: 99%